2021
DOI: 10.3390/jcm10102093
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Assessment of Non-Verbal Auditory Perception in Normal-Hearing Participants and Cochlear Implant Users

Abstract: In the case of hearing loss, cochlear implants (CI) allow for the restoration of hearing. Despite the advantages of CIs for speech perception, CI users still complain about their poor perception of their auditory environment. Aiming to assess non-verbal auditory perception in CI users, we developed five listening tests. These tests measure pitch change detection, pitch direction identification, pitch short-term memory, auditory stream segregation, and emotional prosody recognition, along with perceived intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 125 publications
(220 reference statements)
0
3
0
1
Order By: Relevance
“…Several studies have found mild-to-moderate hearing loss to be related to deficits in vocal emotion recognition ability [19,27,28]), an ability that is not mitigated by hearing aid use [27], but also see [29,30]. However, it has been suggested that what is interpreted as vocal emotion recognition deficits should rather be interpreted as general deficits in prosody recognition (including linguistic and non-linguistic prosody; [30,31]). Concerning recognition of different vocal emotions, Christensen et al found no significant interaction between emotion category and hearing loss [19].…”
Section: Vocal Emotion Recognition Under Mild-to-moderate Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found mild-to-moderate hearing loss to be related to deficits in vocal emotion recognition ability [19,27,28]), an ability that is not mitigated by hearing aid use [27], but also see [29,30]. However, it has been suggested that what is interpreted as vocal emotion recognition deficits should rather be interpreted as general deficits in prosody recognition (including linguistic and non-linguistic prosody; [30,31]). Concerning recognition of different vocal emotions, Christensen et al found no significant interaction between emotion category and hearing loss [19].…”
Section: Vocal Emotion Recognition Under Mild-to-moderate Hearing Lossmentioning
confidence: 99%
“…Goy et al, however, found such an interaction, with sadness being recognized accurately significantly more often compared to anger, disgust, fear and happiness, but not compared to surprise or neutrality. In individuals with hearing loss, confusions between different vocal emotions appear to be much more common in comparison to normal hearing individuals [31].…”
Section: Vocal Emotion Recognition Under Mild-to-moderate Hearing Lossmentioning
confidence: 99%
“…Indeed, despite the considerable advances offered by the cochlear implant (CI) in restoring peripheral hearing, its limited frequency resolution may be responsible for distortion of incoming sensory input. Consequently, users may experience both verbal and nonverbal hearing difficulties (4,5), and have been shown to demonstrate poor to average performance in environmental stimuli recognition tasks (5). Interestingly, CI users do not always complain about environmental sounds.…”
Section: Introductionmentioning
confidence: 99%
“…Тем не менее остается много возможностей для их улучшения [4]. Как отмечают большинство авторов, даже пациенты с наилучшими результатами все еще имеют трудности слухового восприятия в сложных акустических условиях, таких как речь в шуме или в ситуации с одновременно несколькими говорящими [5]. Одну из самых больших проблем для прослушивания у пациентов с кохлеарными имплантатами представляет восприятие музыки [6].…”
unclassified